Cognitive Improvement After Cochlear Implantation in Older Adults With Severe or Profound Hearing Impairment: A Prospective, Longitudinal, Controlled, Multicenter Study. Issue 3 (May 2021) - Mertens, Griet; Andries, Ellen; Claes, Annes J.; Topsakal, Vedat; Van de Heyning, Paul; Van Rompaey, Vincent; Calvino, Miryam; Sanchez Cuadrado, Isabel; Muñoz, Elena; Gavilán, Javier; Bieńkowska, Katarzyna; Świerniak, Weronika; et al.
Abstract : Objective: To compare the cognitive evolution of older adults with severe or profound hearing impairment after cochlear implantation with that of a matched group of older adults with severe hearing impairment who do not receive a cochlear implant (CI). Design: In this prospective, longitudinal, controlled, and multicenter study, 24 older CI users were included in the intervention group and 24 adults without a CI in the control group. The control group matched the intervention group in terms of gender, age, formal education, cognitive functioning, and residual hearing. Assessments were made at baseline and 14 months later. Primary outcome measurements included the change in the total score on the Repeatable Battery for the Assessment of Neuropsychological Status for Hearing impaired individuals score and on its subdomain score to assess cognitive evolution in both groups. Secondary outcome measurements included self-reported changes in sound quality (Hearing Implant Sound Quality Index), self-perceived hearing disability (Speech, Spatial, and Qualities of Hearing Scale), states of anxiety and depression (Hospital Anxiety and Depression Scale), and level of negative affectivity and social inhibition (Type D questionnaire). Results: Improvements of the overall cognitive functioning ( p = 0.05) and the subdomain "Attention" ( p = 0.02) were observed after cochlear implantation in the intervention group; their scores were compared to the corresponding scores in the control group. Significant positive effects of cochlear implantation on sound quality and self-perceived hearing outcomes were found in the intervention group. Notably, 20% fewer traits of Type D personalities were measured in the intervention group after cochlear implantation. In the control group, traits of Type D personalities increased by 13%. Conclusion: Intervention with a CI improved cognitive functioning (domain Attention in particular) in older adults with severe hearing impairment compared to that of the matched controls with hearing impairment without a CI. However, older CI users did not, in terms of cognition, bridge the performance gap with adults with normal hearing after 1 year of CI use. The fact that experienced, older CI users still present subnormal cognitive functioning may highlight the need for additional cognitive rehabilitation in the long term after implantation.